A water-based phenolic epoxy-based thermochromic thermal insulation coating and a preparation method thereof
Through the preparation of water-based phenolic epoxy-based temperature-changing heat-sensitive thermal insulation coatings, combined with hollow glass microbeads and temperature-sensitive color-changing pigments, the shortcomings of existing thermal insulation coatings in terms of heat resistance, flame retardancy and high temperature warning are solved, and more efficient heat insulation and safe high temperature warning are achieved.
Patent Information
- Application Number
- CN202310970193.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-02
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-08-02
AI Technical Summary
Existing thermal insulation coatings are insufficient in long-term temperature resistance, flame retardant and high temperature warnings, and traditional thermal insulation materials are inconvenient to construction, which can easily lead to corrosion and leakage accidents under the pipeline insulation layer.
The water-based phenolic epoxy-based temperature-changing heat-insulating coating is used to improve the heat resistance, flame retardant performance and high-temperature warning ability of the coating through the combination of phenolic epoxy resin and hollow glass microbeads, and the emulsion is prepared through opposite technology to ensure good coating and dispersion of the resin and microbeads.
It significantly improves the corrosion resistance, heat resistance and heat insulation properties of the coating, realizes effective barriers to heat energy transfer, and achieves high temperature warning through temperature-sensitive color-changing pigments, improving operational safety.
Smart Images

Figure BDA0004375038060000081 
Figure BDA0004375038060000091 
Figure BDA0004375038060000092
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of thermal insulation coatings and relates to a method for preparing a water-based phenolic epoxy-based thermochromic thermal insulation coating. Background Art
[0002] At present, the anti-corrosion and heat preservation means of petrochemical refining pipelines or containers are composed of three parts: bottom anti-corrosion layer, middle heat insulation layer, and surface protection layer. The middle heat insulation layer uses traditional heat insulation products, such as asbestos felt, silicate felt, polyurethane sponge, etc. These products are inconvenient to construct and usually require a large thickness to isolate the high temperature inside the pipeline. At the same time, the water absorption rate is high, which is very easy to cause corrosion under the pipeline insulation layer, and it is difficult to detect, and it is very easy to cause accidents such as leakage.
[0003] Therefore, in response to the problems existing in the traditional thermal insulation system of petrochemical pipelines, a new type of thermal insulation coating is designed and prepared, which has excellent high temperature resistance and thermal insulation, good adhesion to the substrate, and excellent water resistance, gasoline resistance and salt spray resistance, in order to solve the difficult problems in the field of petrochemical pipeline insulation.
[0004] At present, the production of thermal insulation coatings mainly adopts the method of adding thermal insulation fillers into resin binders. The thermal insulation fillers mainly include hollow glass microspheres, hollow ceramic microspheres, aerogels, etc.
[0005] The choice of resin as a binder for thermal insulation coatings is very important. It needs to meet the characteristics of good adhesion, good heat resistance and good anti-corrosion performance. The thickness of thermal insulation coatings is generally higher than 2mm, which may be ignited and cause fire. At the same time, the amount of thermal insulation filler added to thermal insulation coatings is large, the viscosity is high, and a large amount of solvent needs to be added to dilute, so the solvent consumption is large. In recent years, the VOC emission restrictions in the coatings industry have become increasingly stringent, and water-based thermal insulation coatings have received attention.
[0006] Among the raw materials used in water-based thermal insulation coatings, the particle size distribution and stability of the emulsion have a great influence on the compatibility of thermal insulation fillers such as glass microbeads in the coating and whether they are well dispersed. The smaller the particle size of the emulsion used, the better the stability, the stronger the coating of the glass microbeads, and the more evenly the glass microbeads are dispersed in the coating and the less likely they are to break. Therefore, the emulsifier suitable for the system is selected, and the particle size distribution and stability of the prepared emulsion meet the use requirements of water-based thermal insulation coatings, so that the resin can be tightly coated around the glass microbeads, and the microbeads can be well dispersed in the coating, so as to have better thermal insulation performance.
[0007] The long-term heat resistance of the cured water-based epoxy resin film commonly used in the anti-corrosion coating industry is lower than 180°C, which is not suitable for applications where the temperature of the flowing medium in the pipeline is high, and its flame retardant properties cannot meet the fire protection requirements. Phenolic epoxy resin has high functionality and high benzene ring content. The long-term heat resistance of the cured paint film can reach 200°C, and it has good flame retardant properties, which meets the heat resistance requirements of thermal insulation coatings.
[0008] However, the hydrophobicity of phenolic epoxy resin is stronger, and the stability of phenolic epoxy emulsion obtained by using the emulsifier of ordinary bisphenol A epoxy resin cannot be guaranteed, so it is necessary to design and select a suitable emulsifier.
[0009] In the chemical industry, the use of thermal insulation layers or thermal insulation coatings can reduce heat loss in the medium in pipes or containers and reduce energy consumption. However, it cannot guarantee that the temperature of the outer wall of the pipe or container will drop below the safe temperature of 60°C for the human body. When human skin is exposed to a temperature of 60°C for more than one minute, it can cause irreversible skin damage. When using traditional thermal insulation coating materials, due to the large thickness, on-site staff can intuitively easily identify that the flowing medium is high temperature and will not touch it to avoid burns. However, when the use of thermal insulation coatings replaces the traditional thermal insulation material coating layer, it is customary for on-site staff to mistakenly believe that it is just an ordinary anti-corrosion coating, and the temperature of the medium in the pipe or container is not high, and burns may occur from mistaken contact with a surface with a temperature higher than 60°C.
[0010] Therefore, the preparation of thermal insulation coatings with good long-term heat resistance, flame retardancy and high temperature warning effects remains a technical challenge in the thermal insulation coating industry. Summary of the invention
[0011] The present invention proposes a method for preparing a water-based phenolic epoxy-based thermochromic thermal insulation coating, aiming to overcome the shortcomings of existing thermal insulation coatings in terms of long-term heat insulation, flame retardancy and insufficient high-temperature warning effects. The epoxy group functionality of phenolic epoxy resin is greater than 2, and phenolic epoxy coatings have a greater cross-linking density and stronger anti-corrosion ability. The fully cured coating film has good corrosion resistance, chemical resistance and heat resistance. By adding thermal insulation fillers, the thermal conductivity of the coating is reduced, and the barrier effect of the coating on heat energy transfer is further improved. By adding thermochromic pigments, when the external temperature of the coating is greater than 60°C, the color of the coating changes, achieving the purpose of high-temperature warning and protecting the safety of operators.
[0012] In order to achieve the above object, the technical solution adopted by the present invention is:
[0013] The water-based phenolic epoxy thermochromic heat-insulating coating is composed of components A and B by weight, wherein component A is as follows: 80-120 parts of phenolic epoxy emulsion, 20-100 parts of heat-insulating filler, 5-10 parts of thermochromic pigment, 10-40 parts of magnesium hydroxide, 10-20 parts of titanium dioxide, 2-8 parts of rock wool fiber, 5-15 parts of cosolvent, 1-5 parts of dispersant, 1-5 parts of defoamer, and 1-20 parts of water. Component B is: 30-100 parts of water-based curing agent.
[0014] The preparation method is:
[0015] (1) Preparation of reactive emulsifier: Epoxy resin E-20 and polyethylene glycol PEG-8000 were weighed and calculated with a certain molar ratio of hydroxyl group to epoxy group. They were added into the reactor in sequence and completely melted at 90°C. Then, the epoxy resin and 0.2% of the total mass of the polyethylene glycol in boron trifluoride ether were added dropwise into the flask using a micro syringe and reacted at a certain speed for 2 hours.
[0016] (2) Preparation of phenolic epoxy emulsion: Take an appropriate amount of phenolic epoxy resin and put it into a reaction container, add a reactive emulsifier, heat it to 60-120°C and keep it warm for 0.5-1h. After the reactive emulsifier is completely melted, add the co-solvent propylene glycol methyl ether to the above reaction container, stir until it is uniform and transparent, and at a speed of 4000r / min, add the first part of water (about 42% of the mass of the phenolic epoxy resin) to the system for phase inversion, and the addition is completed within 10min. After the phase inversion is completed, adjust the speed to 2000r / min, add the second part of water (about 75% of the mass of the phenolic epoxy resin) to the system for dilution, and the addition is completed within 20min. After the addition is completed, continue to disperse for 20min.
[0017] (3) Preparation of thermal insulation coating: Phenolic epoxy emulsion, thermal insulation filler, thermochromic pigment, magnesium hydroxide, titanium dioxide, rock wool fiber, cosolvent, dispersant, defoamer and water were mixed and dispersed evenly using a high-speed disperser at a speed of 1000 r / min for 0.5 h. A water-based curing agent was added to the resulting slurry.
[0018] Furthermore, in the preparation of the emulsifier, the molar ratio of the hydroxyl group to the epoxy group is 1:1-2.
[0019] Furthermore, in the preparation of the emulsifier, the molar ratio of hydroxyl group to epoxy group is preferably 1:1.
[0020] Furthermore, the novolac epoxy resin is a linear phenolic polyglycidyl ether novolac epoxy resin, and the epoxy value is 0.53 to 0.59 eq / 100g.
[0021] Furthermore, the heat-insulating filler is hollow glass microspheres with an average particle size of 60 μm, and the added amount is 10% to 50% of the mass of the entire component.
[0022] Furthermore, the hollow glass microspheres are added in an amount of 10 to 25% of the mass of the waterborne phenolic epoxy-based thermal insulation coating, preferably 20% of the mass of the entire component.
[0023] Furthermore, the color change temperature of the thermochromic filler is 60°C, it is red below 60°C, and turns white above 60°C. The added amount is 5% to 10% of the mass of the entire component.
[0024] Furthermore, the water-based curing agent is an amine curing agent, and the amine hydrogen equivalent is 100 to 450 g / mol.
[0025] Furthermore, the amount of the water-based curing agent added is 1:1 according to the ratio of amine hydrogen equivalent to epoxy equivalent.
[0026] Compared with the prior art, the advantages of the present invention are:
[0027] The phenolic epoxy emulsion prepared by the present invention adopts phase inversion technology. Correlation analysis shows that the conventional phase inversion method is not suitable for the water-based phenolic epoxy resin, and the resin structure in the emulsion is different, and the method and conditions for preparing the emulsion are also different. And how to prepare a suitable emulsifier for the preparation of phenolic epoxy emulsion, which is more conducive to the improvement of the thermal insulation performance of the coating, is the problem solved by the present invention. The raw materials of the present invention are easy to obtain, the preparation process is simple, and the obtained emulsion has good stability, corrosion resistance and heat resistance. Hollow microspheres have good compatibility with the resin system, excellent chemical corrosion resistance, and low thermal conductivity. The hollow microspheres and the thermal insulation performance synergistic effect of the phenolic epoxy resin are utilized to significantly improve the corrosion resistance of traditional thermal insulation coatings and the barrier effect on heat.
[0028] The properties of the obtained phenolic epoxy emulsion:
[0029] (1) Average particle size: 900 nm, distribution index < 0.2.
[0030] (2) Thermal stability: 50°C, no stratification for 72 hours.
[0031] (3) Storage stability: No stratification or demulsification for 6 months.
[0032] (4) The basic physical properties of the varnish film can meet the standard requirements, including impact resistance of more than 70cm and adhesion level 0.
[0033] The properties of the obtained water-based phenolic epoxy-based thermochromic thermal insulation coating are as follows:
[0034] (1) The thermal conductivity of the coating was measured to be around 0.09 W / (m·K).
[0035] (2) In an environment of 60°C, the temperature difference outside the coating is close to 25°C. In an environment of 200°C, the temperature difference outside the coating is close to 100°C.
[0036] (3) When the external temperature of the coating reaches 60°C, the coating color changes from red to white, achieving the purpose of high temperature warning and protecting the safety of operators.
[0037] (4) It has a certain fire retardant effect. After being tested with a 1000℃ flame spray gun for 30 seconds, the coating has good adhesion and no powder falls off the surface. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 Particle size distribution curve of phenolic epoxy emulsion;
[0039] Figure 2 DSC graph of varnish film;
[0040] Figure 3 TG / DTG graph of varnish film under nitrogen atmosphere;
[0041] Figure 4 Histogram of density variation of cured coating of thermal insulation coating;
[0042] Figure 5 TG / DTG graph of thermal insulation coating cured coating in nitrogen atmosphere;
[0043] Figure 6 Schematic diagram of thermal insulation performance test device;
[0044] Figure 7 Thermal insulation performance test curve of thermal insulation paint cured coating;
[0045] Figure 8 Photos of fire performance tests of cured coatings of thermal insulation coatings;
[0046] Fig. 9 SEM image of the cross-sectional morphology of the cured coating of the thermal insulation coating;
[0047] Fig.10 Digital photos of the actual effect test of thermochromic thermal insulation coating. DETAILED DESCRIPTION
[0048] The present invention will now be further described in conjunction with specific embodiments. The following embodiments are intended to illustrate the present invention rather than to further limit the present invention.
[0049] Experimental raw materials: phenolic epoxy resin NPPN-638S: Nan Ya Epoxy Resin (Kunshan) Co., Ltd.; hollow glass microspheres: 3M Company; titanium dioxide: DuPont; magnesium hydroxide: Hefei Zhongke Flame Retardant New Materials Co., Ltd.; rock wool fiber: Langfang Huaneng Building Materials.
[0050] Embodiment 1:
[0051] The emulsifier and the corresponding emulsion were prepared with a molar ratio of hydroxyl to epoxy group of 1:1, and a heat-insulating coating containing 10% hollow glass microspheres was prepared.
[0052] (1) Calculate and weigh the required theoretical mass of epoxy resin E-20 and polyethylene glycol PEG-8000 according to the molar ratio of hydroxyl group to epoxy group of 1:1. Add them into the reactor in sequence and melt them completely at 90°C. Then, add 0.2% of the total mass of the epoxy resin and polyethylene glycol in boron trifluoride ether into the flask with a micro syringe, and react for 2 hours at a certain speed to obtain a reactive emulsifier ER 1-1.
[0053] (2) Take 120g of phenolic epoxy resin and 17.73g (6% of the total mass) of emulsifier ER 1-1 in a reaction container, heat to 90°C and keep warm for 0.5h. After the emulsifier is completely melted, add 17.73g (6% of the total mass) of propylene glycol methyl ether to the above reaction container and stir until it is uniform and transparent. Adjust the speed to 4000r / min, add the first part of water (50g) to the system for phase inversion, and complete the addition within 10min. After the phase inversion is completed, adjust the speed to 2000r / min, add the second part of water (90g) to the system for dilution, and complete the addition within 20min. After the addition is completed, continue to disperse for 20min to obtain a phenolic epoxy emulsion.
[0054] (3) 100g of phenolic epoxy emulsion, 2g of dispersant, 10g of propylene glycol methyl ether, 5g of rock wool fiber, 27.16g of hollow glass microspheres (10% of the total mass), 32g of magnesium hydroxide, 13.57g of titanium dioxide, 1g of defoamer, and 5g of water were mixed and dispersed evenly using a high-speed disperser at a speed of 1000r / min for 1h. 94.318g of water-based curing agent (amine hydrogen equivalent 415g / mol) was added to the dispersed slurry, and the coating was brushed on the steel substrate with a brush. The average thickness of the coating sample was maintained at about 3 mm and measured by a thickness meter. After the coating was cured at room temperature for 7 days, a water-based phenolic epoxy-based thermal insulation coating was obtained.
[0055] Embodiment 2:
[0056] Preparation of thermal insulation coating containing 15% hollow glass microspheres.
[0057] (1) Prepare an emulsifier according to Example 1.
[0058] (2) Prepare phenolic epoxy emulsion according to Example 1.
[0059] (3) 100g of phenolic epoxy emulsion, 2g of dispersant, 10g of propylene glycol methyl ether, 5g of rock wool fiber, 47g of hollow glass microspheres (15% of the total mass), 32g of magnesium hydroxide, 15.6g of titanium dioxide, 1g of defoamer, and 5g of water were mixed and dispersed evenly using a high-speed disperser at a speed of 1000r / min for 1h. 94.318g of water-based curing agent (amine hydrogen equivalent 415g / mol) was added to the dispersed slurry, and the coating was brushed on the steel substrate with a brush. The average thickness of the coating sample was maintained at about 3 mm and measured by a thickness meter. After the coating was cured at room temperature for 7 days, a water-based phenolic epoxy-based thermal insulation coating was obtained.
[0060] Embodiment 3:
[0061] Preparation of thermal insulation coating containing 20% hollow glass microspheres.
[0062] (1) Prepare an emulsifier according to Example 1.
[0063] (2) Prepare phenolic epoxy emulsion according to Example 1.
[0064] (3) 100g of phenolic epoxy emulsion, 2g of dispersant, 10g of propylene glycol methyl ether, 5g of rock wool fiber, 66g of hollow glass microspheres (20% of the total mass), 33g of magnesium hydroxide, 15.6g of titanium dioxide, 1g of defoamer, and 5g of water were mixed and dispersed evenly using a high-speed disperser at a speed of 1000r / min for 1h. 94.318g of water-based curing agent (amine hydrogen equivalent 415g / mol) was added to the dispersed slurry, and the coating was brushed on the steel substrate with a brush. The average thickness of the coating sample was maintained at about 3 mm and measured by a thickness meter. After the coating was cured at room temperature for 7 days, a water-based phenolic epoxy-based thermal insulation coating was obtained.
[0065] Embodiment 4:
[0066] Preparation of thermal insulation coating containing 25% hollow glass microspheres.
[0067] (1) Prepare an emulsifier according to Example 1.
[0068] (2) Prepare phenolic epoxy emulsion according to Example 1.
[0069] (3) 100g of phenolic epoxy emulsion, 2g of dispersant, 10g of propylene glycol methyl ether, 5g of rock wool fiber, 83g of hollow glass microspheres (25% of the total mass), 33g of magnesium hydroxide, 15.6g of titanium dioxide, 1g of defoamer, and 5g of water were mixed and dispersed evenly using a high-speed disperser at a speed of 1000r / min for 1h. 34.09g of water-based curing agent (amine hydrogen equivalent 150g / mol) was added to the dispersed slurry, and the coating was brushed on the steel substrate with a brush. The average thickness of the coating sample was maintained at about 3 mm and measured by a thickness meter. After the coating was cured at room temperature for 7 days, a water-based phenolic epoxy-based thermal insulation coating was obtained.
[0070] Embodiment 5:
[0071] Preparation of water-based phenolic epoxy-based thermochromic thermal insulation coating.
[0072] (1) Prepare an emulsifier according to Example 1.
[0073] (2) Prepare phenolic epoxy emulsion according to Example 1.
[0074] (3) 100g phenolic epoxy emulsion, 2g dispersant, 10g propylene glycol methyl ether, 5g rock wool fiber, 66g hollow glass microsphere, 5g thermochromic pigment, 33g magnesium hydroxide, 15.6g titanium dioxide, 1g defoamer, 5g water are mixed and evenly dispersed with a high-speed disperser, and the rotating speed is 1000r / min, and the time is 1h. 94.318g water-based curing agent (amine hydrogen equivalent 415g / mol) is added to the slurry obtained by dispersion, and the coating is brushed on the steel substrate with a brush. The average thickness of the coating sample remains on about 3 mm, and is measured by a thickness gauge. After the coating is cured at room temperature for 7 days, a water-based phenolic epoxy-based thermochromic heat-insulating coating is obtained.
[0075] Comparative Example 1:
[0076] Preparation of ordinary E-51 epoxy emulsion containing 20% hollow glass microspheres for thermal insulation coating.
[0077] (1) 100g E-51 epoxy emulsion, 2g dispersant, 10g propylene glycol methyl ether, 5g rock wool fiber, 66g hollow glass microspheres (20% of the total mass), 33g magnesium hydroxide, 15.6g titanium dioxide, 1g defoamer, and 5g water were mixed and dispersed evenly using a high-speed disperser at a speed of 1000r / min for 1h. 79.81g water-based curing agent (amine hydrogen equivalent 415g / mol) was added to the dispersed slurry, and the coating was brushed on the steel substrate with a brush. The average thickness of the coating sample was maintained at about 3 mm and measured by a thickness gauge. The coating was cured at room temperature for 7 days.
[0078] Comparative Example 2:
[0079] The emulsifier and the corresponding emulsion were prepared with a molar ratio of hydroxyl to epoxy group of 1:1.5, and a heat-insulating coating containing 20% hollow glass microspheres was prepared.
[0080] (1) Calculate and weigh the theoretical mass required for epoxy resin E-20 and polyethylene glycol PEG-8000 according to the molar ratio of hydroxyl group to epoxy group of 1:1.5. Add them into the reactor in sequence and melt them completely at 90°C. Then, add 0.2% of the total mass of the epoxy resin and polyethylene glycol in boron trifluoride ether into the flask with a micro syringe, and react for 2 hours at a certain speed to obtain a reactive emulsifier ER 1-1.5.
[0081] (2) Take 120g of phenolic epoxy resin and 17.73g (6% of the total mass) of emulsifier ER 1-1.5 in a reaction container, heat to 90°C and keep warm for 0.5h. After the emulsifier is completely melted, add 17.73g (6% of the total mass) of propylene glycol methyl ether to the above reaction container and stir until it is uniform and transparent. Adjust the speed to 4000r / min, add the first part of water (50g) to the system for phase inversion, and complete the addition within 10min. After the phase inversion is completed, adjust the speed to 2000r / min, add the second part of water (90g) to the system for dilution, and complete the addition within 20min. After the addition is completed, continue to disperse for 20min to obtain a phenolic epoxy emulsion.
[0082] (3) 100g of the above-obtained phenolic epoxy emulsion, 2g of dispersant, 10g of propylene glycol methyl ether, 5g of rock wool fiber, 66g of hollow glass microspheres (20% of the total mass), 33g of magnesium hydroxide, 15.6g of titanium dioxide, 1g of defoamer, and 5g of water were mixed and dispersed evenly using a high-speed disperser at a speed of 1000r / min for 1h. 94.318g of water-based curing agent (amine hydrogen equivalent 415g / mol) was added to the dispersed slurry, and the coating was applied on the steel substrate with a brush. The average thickness of the coating sample was maintained at about 3 mm and measured by a thickness gauge. The coating was cured at room temperature for 7 days.
[0083] Comparative Example 3:
[0084] The emulsifier and the corresponding emulsion were prepared with a molar ratio of hydroxyl to epoxy group of 1:1.7, and a heat-insulating coating containing 20% hollow glass microspheres was prepared.
[0085] (1) Calculate and weigh the required theoretical mass of epoxy resin E-20 and polyethylene glycol PEG-8000 according to the molar ratio of hydroxyl group to epoxy group of 1:1.7. Add them into the reactor in sequence and melt them completely at 90°C. Then, add 0.2% of the total mass of the epoxy resin and polyethylene glycol in boron trifluoride ether into the flask with a micro syringe, and react for 2 hours at a certain speed to obtain a reactive emulsifier ER 1-1.7.
[0086] (2) Take 120g of phenolic epoxy resin and 17.73g (6% of the total mass) of emulsifier ER 1-1.7 in a reaction container, heat to 90°C and keep warm for 0.5h. After the emulsifier is completely melted, add 17.73g (6% of the total mass) of propylene glycol methyl ether to the above reaction container and stir until it is uniform and transparent. Adjust the speed to 4000r / min, add the first part of water (50g) to the system for phase inversion, and complete the addition within 10min. After the phase inversion is completed, adjust the speed to 2000r / min, add the second part of water (90g) to the system for dilution, and complete the addition within 20min. After the addition is completed, continue to disperse for 20min to obtain a phenolic epoxy emulsion.
[0087] (3) 100g of the above-obtained phenolic epoxy emulsion, 2g of dispersant, 10g of propylene glycol methyl ether, 5g of rock wool fiber, 66g of hollow glass microspheres (20% of the total mass), 33g of magnesium hydroxide, 15.6g of titanium dioxide, 1g of defoamer, and 5g of water were mixed and dispersed evenly using a high-speed disperser at a speed of 1000r / min for 1h. 94.318g of water-based curing agent (amine hydrogen equivalent 415g / mol) was added to the dispersed slurry, and the coating was applied on the steel substrate with a brush. The average thickness of the coating sample was maintained at about 3 mm and measured by a thickness gauge. The coating was cured at room temperature for 7 days.
[0088] Table 1
[0089]
[0090]
[0091] Table 2
[0092]
[0093] Table 3
[0094]
[0095] Table 1 shows the comprehensive properties of the emulsion corresponding to Example 1. The emulsion has good stability under centrifugation, the presence of calcium ions and heating conditions, and the emulsion can be stored at room temperature for more than 180 days.
[0096] The particle size distribution curve of the phenolic epoxy emulsion prepared in Example 1 is as follows: Figure 1As shown, the particle size of the emulsion is distributed at 900nm, and the distribution index (PDI) is 0.186. The particle size of the emulsion is small and the distribution is uniform. The particle size of the emulsion prepared in Comparative Example 3 is larger and the particle size distribution is wider. This shows that the emulsifier ER 1-1 prepared with a hydroxyl and epoxy molar ratio of 1:1 has a better emulsification effect on phenolic epoxy resin, a small emulsion particle size, a narrow distribution, a stronger coating for glass microspheres, and a more uniform dispersion of microspheres in the coating, which is more conducive to improving thermal insulation performance.
[0097] Figure 2 is the DSC test curve of the emulsion cured paint film, and the glass transition temperature (T g ) is 82.28°C, and the glass transition temperature of the emulsion varnish film prepared in Example 1 is 98.78°C. This is because compared with ordinary bisphenol A epoxy resin, the increase in the functionality of the phenolic epoxy resin and the introduction of the rigid benzene ring structure increase the crosslinking density of the cured product and the rigidity of the molecular chain segments, making its glass transition temperature higher, thereby improving the hardness, strength, heat resistance and other properties, and maintaining good mechanical properties and stability in a high temperature environment, and is not prone to deformation and damage, while epoxy resins with low glass transition temperatures are prone to softening and failure.
[0098] Figure 3 is the thermogravimetric analysis of the varnish film. The T 5% 303.5℃, T 50% The T of the emulsion varnish film prepared in Comparative Example 1 under nitrogen atmosphere was 381.1°C and the residual mass was 16.33%. 5% is 263.4℃, T 50% The temperature of the emulsion curing system of Comparative Example 1 is 389.3℃, and the residual mass is 11.21%. Between 400℃ and 450℃, a larger peak value appears in the emulsion curing system of Comparative Example 1, that is, the thermal decomposition rate of the coating is faster at this temperature. The overall results show that the phenolic epoxy emulsion curing material has better thermal stability.
[0099] Figure 4 The density change bar graph of the cured coating of the thermal insulation coating shows that the thermal conductivity of the thermal insulation material is highly correlated with the density. Generally, the material with a lower density has a lower thermal conductivity and better thermal insulation performance. It can be seen that as the content of the hollow glass microspheres increases, the coating density gradually decreases. The coating density of Example 4 begins to rise. The density of the system of Example 3 is the lowest, which is 237.38 kg / m 3 .
[0100] Figure 5This is a thermal gravimetric analysis of the thermal insulation coating. The cured paint films of the thermal insulation coating prepared with different hollow glass microsphere contents all have a similar thermal decomposition process. The fastest thermal decomposition rate of the coating is around 350°C. The thermal decomposition rate of Example 1 is faster, and the final residual mass is lower. As the content of hollow glass microspheres increases, the final residual mass of the coating gradually increases. The fire retardant properties of the coating can be used as a reference indicator for the high temperature resistance of the material. The amount of residual mass reflects the level of flame retardant properties. Coatings with high residual mass will produce a dense carbon layer when burned at high temperatures, which hinders the transfer of oxygen and heat. When the content of hollow glass microspheres is higher than 10%, the T 5% The residual mass at 800°C and 800°C gradually increases with the increase of the hollow glass microsphere content, among which the T 5% It is relatively high, reaching above 290°C, and the residual mass at 800°C is more prominent, thus showing good thermal stability and fire retardant ability.
[0101] Figure 7 The thermal insulation performance test of water-based phenolic epoxy thermal insulation coating is carried out. During the test, the temperature is regulated and heated from 60°C to 200°C to test the difference (ΔT) between the internal temperature (T0) of the coating device and the external temperature (T1) of the coating. It can be seen that with the increase of T0, ΔT shows a trend of increasing, and the growth rate of Example 3 is larger, and the external temperature of the coating is much lower than the internal temperature of the device, indicating that the water-based phenolic epoxy thermal insulation coating has a good barrier effect on heat energy. The reason is that the hollow glass microspheres are hollow structures. When heat is conducted through the glass microspheres, the path of heat conduction becomes significantly longer. On the other hand, the cross-linked network structure formed in the phenolic epoxy resin cured product, the addition of hollow glass microspheres to the coating can naturally form layers of dense thermal insulation films, effectively blocking the transfer of heat. However, the hollow glass microspheres have poor compatibility with the epoxy emulsion of Comparative Example 1, and the cross-linking density of ordinary bisphenol A epoxy resin is low, resulting in the internal structure of the prepared paint film coating being not tight, the heat energy transmission rate becoming faster, and the thermal insulation performance decreasing. However, the emulsions obtained in Comparative Examples 2 and 3 have larger particle sizes, wider particle size distribution, poorer stability, poorer coating properties for glass microbeads, and uneven dispersion of microbeads in the coating, resulting in certain microscopic cracks inside the coating, thereby affecting the thermal insulation performance of the coating.
[0102] Figure 8 The fire retardant performance test of the water-based phenolic epoxy thermal insulation coating was conducted at 1000°C for 30 seconds. After testing, the sample of Example 3 had good adhesion, no powder appeared on the surface, and no fire occurred. In comparison, the coating of Comparative Example 1 cracked, had poor adhesion, had powder on the surface, and the coating became loose.
[0103] Example 3 exhibits good heat resistance and has a certain fire retardant effect.
[0104] Fig. 9 This is a cross-sectional morphology analysis of water-based phenolic epoxy-based thermal insulation coatings. The test results show that, taking the thermal insulation coating obtained in Example 3 as an example, the hollow glass microspheres have good compatibility with the phenolic epoxy emulsion (Example 1), are evenly dispersed in the coating, and have a low breakage rate. Comparative Examples 1 and 3 show obvious agglomeration and uneven dispersion. Therefore, the emulsifier ER 1-1 prepared with a 1:1 ratio of hydroxyl and epoxy groups has the best emulsification effect on phenolic epoxy resins, and the phenolic epoxy emulsion finally obtained has the best coating property for glass microspheres. The glass microspheres are more evenly dispersed in the coating, which is beneficial to improving the thermal insulation and fireproof properties.
[0105] Fig.10 This is the actual color change effect diagram of the water-based phenolic epoxy-based temperature-sensitive color-changing thermal insulation coating in Example 5. It can be seen that when the external temperature of the coating reaches 60°C, the color of the coating changes from the original red to white. When the working device is running and an operator approaches, the purpose of early warning can be achieved.
Claims
1. A water-based phenolic epoxy-based thermochromic thermal insulation coating, characterized in that: The composition is A and B components, wherein the A component is as follows: 80-120 parts of phenolic epoxy emulsion, 20-100 parts of thermal insulation filler, 5-10 parts of thermochromic pigment, 10-40 parts of magnesium hydroxide, 10-20 parts of titanium dioxide, 2-8 parts of rock wool fiber, 5-15 parts of cosolvent, 1-5 parts of dispersant, 1-5 parts of defoamer, and 1-20 parts of water; the B component is: 30-100 parts of water-based curing agent; the thermal insulation filler is hollow glass microspheres with an average particle size of 60 μm; the color change temperature of the thermochromic pigment is 60°C, red below 60°C, and white above 60°C; The preparation steps of phenolic epoxy emulsion are as follows: (1) The preparation steps of the reactive emulsifier are as follows: adding epoxy resin and polyethylene glycol into a reaction container at a molar ratio of epoxy group to hydroxyl group of 1:1, and heating until completely melted; adding boron trifluoride etherate dropwise into the reaction container, heating and reacting for 2 hours to obtain a reactive emulsifier; the epoxy resin is solid bisphenol A type epoxy resin E-20; the polyethylene glycol used is PEG-8000; (2) putting a phenolic epoxy resin into a reaction container, adding the reactive emulsifier prepared in step (1), heating to 60-120° C. and keeping the temperature constant. After the reactive emulsifier is completely melted, adding a cosolvent to the reaction container and stirring until the mixture is uniform and transparent. The phenolic epoxy resin is a linear phenolic polyglycidyl ether phenolic epoxy resin having an epoxy value of 0.53-0.59 eq / 100g. (3) Under stirring, the first portion of deionized water is added dropwise to the system to perform phase inversion; after the phase inversion is completed, the second portion of deionized water is added dropwise to the system to dilute it, and after the addition is completed, the system is dispersed to obtain a phenolic epoxy emulsion.
2. The water-based phenolic epoxy-based thermochromic thermal insulation coating according to claim 1, characterized in that: The boron trifluoride ether accounts for 0.2% of the total mass of the epoxy resin and the polyethylene glycol.
3. The water-based phenolic epoxy-based thermochromic thermal insulation coating according to claim 1, characterized in that: The hollow glass microspheres are added in an amount of 10-25% of the mass of the water-based phenolic epoxy-based thermal insulation coating.
4. The water-based phenolic epoxy-based thermochromic heat-insulating coating according to claim 1, characterized in that: The cosolvent is propylene glycol methyl ether.
5. The water-based phenolic epoxy-based thermochromic heat-insulating coating according to claim 1, characterized in that: The water-based curing agent is a water-based amine curing agent, and the amine hydrogen equivalent is 100-450 g / mol.
6. The method for preparing the water-based phenolic epoxy-based thermochromic heat-insulating coating according to any one of claims 1 to 5, characterized in that: The specific steps are as follows: mix the phenolic epoxy emulsion, thermal insulation filler, thermochromic pigment, magnesium hydroxide, titanium dioxide, rock wool fiber, cosolvent, dispersant, defoamer and water in component A, and disperse them evenly with a high-speed disperser at a speed of 1000 r / min for 0.5 h, and add the water-based curing agent of component B to the obtained slurry.
Citation Information
Patent Citations
Heavy-duty anti-corrosion phenolic epoxy coating
CN102321423A
Anticorrosive and antibacterial novolac epoxy resin powdery paint
CN103382354A